3D Spectral element model with a space-decoupling technique for the response of transversely isotropic pavements to moving vehicular loading. Issue 11 (2nd November 2022) - Man, Jianhong; Yan, Kezhen; Miao, Yu; Liu, Yang; Yang, Xu; Diab, Aboelkasim; You, Lingyun
ABSTRACT: This study aims to extend the spectral element technique to the three-dimensional (3D) mechanical response of the multi-layered transversely isotropic structure under a moving vehicular load and improve the pavement structural design framework. Details of the mathematical derivation and implementation of the analytical solution were presented. It shall be noted that, neither purely longitudinal nor purely transverse waves exist in the transversely isotropic medium which adds complexity to tackle this problem during analysis of trafficked pavement structures. Therefore, the current study decoupled the governing equations into out-of-plane motion and in-plane motion by using a space-decoupling technique. Numerical results indicated that the proposed spectral element model is reliable, accurate and efficient. Moreover, the interlayer condition between adjacent layers, the load speed, frequency, and the transversely isotropic property of finite and infinite layers significantly affect the flexible pavement structure's dynamic responses.